Psychometric properties of the reading self-efficacy scale in Peruvian students aged 10 to 16 years - Morales-García, Wilter C.; Muñante-Subauste, Yovanna Ysabel; Sairitupa Sanchez, Liset Z.; Morales-García, Sandra B.; Rivera-Lozada, Oriana; Cunza Aranzábal, Denis Frank (Frontiers in Education, 2024)
Background: Reading self-efficacy is a key factor for students' academic performance and motivation and given the low reading performance of Peruvian students compared to the average, it is crucial to understand and improve their reading self-efficacy. Objective: To evaluate the psychometric properties of the Reading Self-Efficacy Scale in a Peruvian sample. Methodology: Using a sample of 560 students aged 10 to 16 (M = 13.5, SD = 1.93), confirmatory factor analysis (CFA) and genderspecific invariance analysis were conducted. Results: A two-dimensional, second-order model was taken into consideration. Significant differences were discovered in gender invariance, suggesting that the scale is comparable between the genders. Conclusion: The validation of the Reading Self-Efficacy Scale in the Peruvian context provides a useful tool to assess and develop Peruvian students' reading self-efficacy, with implications for professional practice and educational policy.